PENGARUH MOTIVASI DAN MINAT BELAJAR TERHADAP KOMUNIKASI KEMAMPUAN STATISTIK MAHASISWA (VIRTUAL) FKIP USI PEMATANGSIANTAR TA 2021/2022 - Wilson Sitopu, Joni; Rosenta Purba, Ika (Jurnal Metabio, 2021)
The problem in this study is that online learning has decreased student motivation and interest, with only a few participating and being active in learning. The purpose of this study was to determine the influence of learning motivation and interest on the communication skills of statistical students (Virtual) at the Faculty of Teacher Training and Education, University of Indonesia (USI), Pematangsiantar, in the 2021/2022 academic year. This research is descriptive quantitative, with conclusions drawn through statistical analysis. The population and sample in this study were all fourth-semester students of the Biology Education study program at the Faculty of Teacher Training and Education, University of Indonesia (USI), Pematangsiantar, in the 2021/2022 academic year. Data were obtained through a questionnaire. The questionnaire was previously tested for data normality and linearity. The data analysis techniques used were simple linear regression analysis, t-test, R2 test, and F-test. The conclusion from the F-test was that F = 4.510, with a Sig. (2-tailed) value of 0.020, less than 0.05 (5%). This means that Ho is rejected and Ha is accepted. In conclusion, learning motivation significantly influences the statistical communication skills of (Virtual) students at the Faculty of Teacher Training and Education, University of Indonesia (USI) Pematangsiantar in the 2021/2022 academic year. The coefficient of determination obtained was 0.195. Based on the results of a simple linear regression test, Y = 58.300 + 0.119 X1 + 0.325 X2.